Pengembangan E-Modul Reaksi Reduksi dan Oksidasi Berbasis Discovery learning untuk Meningkatkan Hasil Belajar Peserta Didik Kelas X MIPA SMA Negeri 11 Bone - Nurhidayanti, Nurhidayanti; Anwar, Muhammad; Danial, Muhammad (Program Pasca Sarjana UNM, 2022)
This study is a development research, which aims at developing e-module of reduction and oxidation reactions based on discovery learning, which is valid, practical, and effective. The development model used was 4-D development model consisted of four stages, namely defining, design, development, and dissemination. The e-module developed was validated by two experts. Then, it was tested to 30 students of grade X MIPA at SMAN 11 Bone. The results of the study reveal that the e-module developed has met a valid, practical, and effective criteria. The e-module is stated as valid based on the validation result of e-module with the average 3.92, which is in very valid category. The e-module is stated as practical based on (1) the implementation of e-module with 1.88 which is in fully implemented category, (2) the teacher’s response with the average 92.71, which is in very practical category, and (3) the students’ response with the average 88.76, which is in vry practical category. The e-module is stated as effective based on the result of learning outcomes with a class completeness percentage of 83.33%. The e-module developed consists of the cover, preface, table of contents, glossarium, conceptual maps, core competence, basic competence, competence achievement indicators, review of reduction and oxidation reactions material, requirement material, e-module manual, workbook 1, 2, and 3, evaluation, and references.